Website Technology Implementation in Stock Management for Enhanced Operational Efficiency: Bismika Tani Case Study - Ahmadi, Thoriq; Jazuli, Ahmad; Fiati, Rina (STMIK Banjarbaru, 2025)
This study develops a web-based Stock and Sales Management Information System to improve accuracy, speed up transactions, and support real-time reporting in the retail sector. This system includes recording incoming and outgoing stock, product registration, sales recording, and report generation, and applies the Just-In-Time (JIT) concept to reduce excess stock and storage costs. Developed using the Waterfall method, the design uses UML, and is implemented with PHP Native and MySQL. Usability testing using the System Usability Scale (SUS) obtained a total sco re of 815 from 9 respondents, with an average of 90.56, categorized as